Analysis of Damage to Exhaust Valve in Auxiliary Engine Number 3 For Smooth Operation n The Mt. Kurau - Ofianda R, Muhammad; Simatupang, Desamen; Dwiyani, Nurinda; Gadji, Fahmi Umasan (Greenation International Journal of Engineering Science, 2024)
The exhaust valve is a component that functions apart from being a way out for combustion residue in the combustion chamber, it also plays a role so that the combustion chamber remains airtight during the compression stroke and the effort stroke. The performance of the exhaust valve greatly affects the power generated by the auxiliary engine. A tight exhaust valve is very important so that the combustion products in the cylinder do not leak into the exhaust manifold so that the performance of the auxiliary engine becomes optimal and the role of the auxiliary engine as the heart of a ship can supply electricity on board properly. The research method used is qualitative with qualitative descriptive data analysis techniques and data collection techniques through observation, interviews, and documentation studies. An indication of damage to the exhaust gas valve is the high temperature of the exhaust gas, as well as abnormal engine sound. After analysis, several causes were found, namely the use of inappropriate spare parts, fatigue in the exhaust gas valve, incomplete combustion in the combustion chamber. Then solve the problem which results in optimal exhaust valve performance so that the performance of the auxiliary engine is good.